SISTEM INFORMASI INVENTORY, PEMBELIAN, DAN PENJUALAN BARANG MENGGUNAKAN METODE WATERFALLSTUDI KASUS : TOKO SEMBAKO AA - Muhammad Izzadin Kaffa (2023)
AA Grocery store is a store engaged in the sale and purchase of daily staples. The AA Grocery Store still uses a manual system. With the increasing number of customers, the number of transactions that attack the store also increases in managing inventory data and sales and purchase transactions. As a result, there are problems in making reports on purchases and sales, as well as information regarding late stocks. For this reason, the author aims to design a system that is capable of nine inventory statuses and generates reports on purchases and sales. To achieve this goal, a web site Inventory Information System, Purchasing and Sales of goods was designed. The development method used is the waterfall method, which involves the stages of needs analysis, design, implementation, testing and maintenance of the system. This system is designed with a database to store information about stock, purchases, and sales, and has an intuitive user interface. The implementation of this system uses HTML and CSS for website display pages, while the PHP programming language and XAMPP server use the MySQL database. This designed system can improve the management of inventory information, transaction efficiency, and better decision making for grocery store owners.